Does agricultural value added induce environmental degradation? Empirical evidence from an agrarian country - Mary O. Agboola; Festus V. Bekun (African Governance and Development Institute (AGDI), 2019)
This study empirically investigates the agriculture-induced environmental Kuznets curve (EKC) hypothesis in an agrarian framework. Annual time series data from 1981−2014 was employed using Augmented Dickey−Fuller and the Phillips−Perron (PP) unit root test complemented by the Zivot and Andrews unit root test that accounts for a single structural break to ascertain stationarity properties of variables under consideration. For the cointegration analysis, an autoregressive distributive lag methodology and the recent novel Bayer and Hanck combined cointegration technique is employed. For the direction of causality, the Granger causality test is used as estimation technique. Empirical findings lend support for the long-run equilibrium relationship among the variables under consideration. This study also validates the inverted U-shaped pattern of EKC for the case of Nigeria, affirming that Nigeria remains at the scale-effect stage of its growth trajectory. Further empirical results show that foreign direct investment attraction helps mitigate carbon emissions in Nigeria. Based on these results, several policy prescriptions on the Nigerian energy mix and agricultural operations in response to quality of the environment were suggested for policymakers, stakeholders, and environmental economists that formulate and design environmental regulations and strategies to realise the Goal 7 of sustainable development goals (SDGs)
Keywords: C32; Q1; Q4; Q5; 330; Agriculture ecosystem; Energy consumption; Granger Causality; EKC; Nigeria